On the origin of forward–backward multiplicity correlations in pp collisions at ultrarelativistic energies - L.V. Bravina (Physics Letters B, 2018)
We study multiplicity correlations of hadrons in forward and backward hemispheres in pp inelastic interactions at energies 200 GeV≤s≤13 TeV within the microscopic quark–gluon string model. The model correctly describes (i) the almost linear dependence of average multiplicity in one hemisphere on the particle multiplicity in other hemisphere in the centre-of-mass frame; (ii) the increase of the slope parameter bcorr with rising collision energy; (iii) the quick falloff of the correlation strength with increase of the midrapidity gap; (iv) saturation of the forward–backward correlations at very high multiplicities. Investigation of the sub-processes on partonic level reveals that these features can be attributed to short-range partonic correlations within a single string and superposition of several sub-processes containing different numbers of soft and hard Pomerons with different mean multiplicities. If the number of Pomerons in the event is fixed, no forward–backward correlations are observed. Predictions are made for the top LHC energy s=13 TeV.